Routing strategies for underwater wireless communication: a taxonomy. (8th July 2021) - Manikandan, T.T.; Sukumaran, Rajeev; Raj, M.R. Christhu; Saravanan, M.
In this research article, we present the broad classification and exhaustive review of the various routing protocols available for underwater wireless communication. In this work, we addressed the various challenges of underwater communication. To present the current state of development in routing strategies for the UWSN, we have chosen a unique approach. Here, the comparison between routing protocols is done purely based on the design perceptive and the specific issue those protocols address. In terms of design, the routing protocols are classified into: 1) non-cross layer; 2) cross layer protocols. Similarly, issues such as: 1) node mobility; 2) energy balancing; 3) channel condition; 4) energy consumption; 5) void region were taken into consideration for the comparison of a broad range of underwater routing strategies. The observation presented from this analysis is worthy for the future researchers and the network designers to work on improving the effectiveness of the routing decisions in a challenging underwater environment.